Length-weight relationships of 15 fish species from Tembeling River, Pahang, Malaysia - Zulkafli, A. R.; Azmai, Mohammad Noor Amal; Shohaimi, Shamarina; Mustafa, A.; Ghani, A. H.; Hashim, Syaratul Emma; Anuar, M. I.; Ayub, Sikander (Blackwell Verlag GmbH, 2016)
This study reports the length–weight relationships (LWR) of 15 fish species from Tembeling River, Pahang, Malaysia. The river flows adjacent to the National Park, Pahang, and supplies fishes for local consumption. In addition, this river also functions as a main water body for protection and breeding of commercial fish species. A total of eight LWRs were unknown to FishBase, and five new maximum lengths were identified from the study.